Development of astronomy - Shellenbaum,Edward (My University, 1897)
Introduction: Astronomy is both a new and an old science. It is old in the sense that is has been studied in ages gone by, by the oldest nations that ever existed, as the Chaldeans, Romans, Egyptians, and many others, without regard as to the correctness of the beliefs and theories of those times; though to them it was satisfactory, just as much so, as we believe our theory of today is true. It is a new science in the sense that we discard the beliefs of the ancients and cling to the present belief or theory, which has been adopted at a comparatively recent date. But in a study of the development of this subject we must take into consideration the ancient astronomy and see how it is related to modern astronomy and how modern astronomy grew out of it. Astronomy originated under three different heads, each having a separate origin, but all depending upon each other and forming one science. The first kind that originated is “observational” or “practical” astronomy. It relates to the facts of all astronomical phenomena, without regard to the cause of them, and was first practiced and studied by the early Chaldeans and Chinese. The second is called “theoretical” or “gravitational” astronomy. It deals with the cause of all phenomena with a view of finding the shy and where fore of it
Citation: Shellenbaum,Edward. Development of astronomy. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Astronomy; Observational astronomy; Theoretical astronomy; Theses; Manuscripts (documents)